Estimating the Distributional Impact of Increasing Taxes on Tobacco Products in Armenia : Results from an Extended Cost-Effectiveness Analysis - Postolovska, Iryna; Lavado, Rouselle F.; Tarr, Gillian; Verguet, Stephane (World Bank, Washington, DC, 2017)
At present, tobacco taxes in Armenia are among the lowest in Europe and Central Asia. Global experience has shown that increasing taxes on tobacco is one of the most cost-effective public health interventions. This is particularly relevant for Armenia, where smoking is among the leading risk factors of mortality among the population.